Animal Rights In Islam: Sarra Tlili's Criticism of the Anthropocentric Reading of the Qur'an - Yasser, Muhammad; Putra, Alven; Qardlawi, Muhammad Yusuf (AL QUDS : Jurnal Studi Alquran dan Hadis, 2024)
This study raises the theme of criticism of anthropocentric readings implemented in the Qur'an, as Sarra Tlili often voices in his various scientific works and seminars. As commonly known, anthropocentrism (the dominant paradigm of the modern age) is receiving widespread criticism because it is considered the root of the global environmental crisis and various forms of violence against animals. Anthropocentric reading of the Qur'an itself has given birth to a biased view of nature and non-human animals so that they are only assessed from the aspect of their use for human interests (instrumentalism) as God's golden children (favoritism). As an alternative, Tlili (re)promotes theocentrism and ecocentrism which are considered more in line with the cosmology of the Qur’an. This research itself uses the hermeneutic verstehen method and active reading techniques which are carried out on various works of Tlili regarding the research theme. This research concludes that it is necessary to reinterpret some of the core concepts in the Qur'an as Tlili did so that it does not give rise to biased views of nature and various forms of violence against non-human animals.